Heavy silicone oil tamponade: a multicentre experience. Issue 1 (8th December 2022) - Davidson, Max; Dowlut, Samir; Zhang, Jufen; Naderi, Khayam; Sandinha, Teresa; Wood, Megan Kay; Schneiders, Matthew; Saidkasimova, Shohista; Peart, Shamfa; Chaudhuri, Ray; Gunda, Manish; Saeed, Manzar; et al.
Abstract : Objective: To report multicentred use of the heavy silicone oil Densiron 68 for anatomical reattachment following rhegmatogenous retinal detachment (RRD) repair and its associated complications. Methods and analysis: Patients from seven vitreoretinal units within the UK that underwent RRD repair with Densiron 68 between January 2015 and December 2019 were identified. Primary outcome measures were primary and final reattachment rate, retained Densiron and failure rate. Secondary outcome measures were duration of tamponade, final visual acuity (VA) and complications of heavy silicone oil. Results: 134 eyes of 134 patients were involved in the study. Primary surgical success was achieved in 48.5%, while a final reattachment rate of 73.4% was observed. The mean duration of Densiron 68 tamponade was 139.5 days. Mean final VA was 1.01 (range 0–2.9). 8 eyes (6.0%) required long-term topical steroids for anterior uveitis, whereas none of the eyes required long-term pressure-lowering treatment. Emulsification rate was 10.7% (6 eyes). Conclusion: This is the largest real-world study on Densiron 68 in the UK. Densiron 68 facilitates tamponade of inferior retinal pathology and may be considered as an option for tamponade of inferior retinal pathologies.